Collagen Characterization in a Model of Nonalcoholic Steatohepatitis with Fibrosis; A Call for Development of Targeted Therapeutics - Pellicano, Anthony J. (Molecules, 2021)
Left untreated, nonalcoholic fatty liver disease can progress to nonalcoholic steatohepatitis (NASH), fibrosis, and end-stage liver disease. To date, few if any therapies have proven effective against NASH with fibrosis. Quantification and qualification of hepatic scar might enable development of more effective targeted therapies. In a murine model of NASH induced by diet, we characterized fibrillar collagen deposition within the hepatic parenchyma. At harvest, livers from the modified diet cohort exhibited NASH with fibrosis. Transcriptomic analysis of hepatic tissue revealed increased col1a1, col1a2, and col3a1, each of which correlated directly with hepatic hydroxyproline content. Circular polarized microscopic analysis of Picrosirius red-stained liver sections revealed deposition of collagen type I within the parenchyma. Development of therapeutics designed to mitigate collagen type I accumulation might prove effective in NASH with fibrosis.